Some solutions for implementing social assistance and functional rehabilitation for children with autism - Tran, Thi Hai Yen (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
Vietnam has a tradition of "helping each other in difficulties," but efforts to implement social assistance and functional recovery for children with autism in Vietnam are still lacking. In implementing social support and rehabilitation for autistic children, there are some practical barriers, such as the legal framework in the provisions of the Law on Persons with disabilities 2010 which still has certain gaps in social support and rehabilitation for autistic children. The Party and State’s policies have initially paid attention to autistic children but there is still a lack of implementation conditions, and there is still some incomplete awareness of autistic children in general; stigma against persons with disabilities, discrimination against persons with disabilities, social work still has some unprofessional points. Internal barriers of autistic children such as the inability to live independently without a caregiver nearby. This article examines in-depth some solutions for implementing social assistance and functional recovery for children with autism in Vietnam today.